Analisis Frasa Teks Narasi pada Buku Pembelajaran IPS Kelas 8 Kurikulum Merdeka - Diah Ayu Wijayanti; Yumna ‘Aqilah; Iyas Rahmawati; Wahyu Ningrum; Asep Purwo Yudi Utomo; Muhammad Sabbardi (Pusat riset dan Inovasi Nasional, 2023)
Syntax is a branch of linguistics that studies grammar in an utterance. One of the objects of study of syntax is phrases. Phrases are grammatical units consisting of two or more words that do not exceed the function limit. This study aims to use phrases that focus on noun phrases, verb phrases, and adjective phrases in narrative texts in social studies learning books for class VII of the independent curriculum. This study used a descriptive qualitative data analysis method by searching, finding, determining, and analyzing the phrases in the narrative text of social studies learning books for class VIII of the independence curriculum. In analyzing the data using the approach of theoretical study of syntax and using the study of documents as a method of data collection. As for the results obtained from this analysis in the form of finding seven noun phrases as the most used phrases in the text, three verb phrases, and five adjective phrases that are appropriate to their respective uses. It is hoped that this research will help many people, especially those pursuing education, better understand the different types of verb phrases, noun phrases, and adjective phrases in narrative text sentences.